2D AND 3D MASS TRANSFER SIMULATIONS IN LYRAE SYSTEM - Nazarenko, V. V.; Glazunova, L. V.; Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
2D and 3D mass transfer simulations of the mass transfer in β Lyrae binary system. We have received that from a point L3 40 percent of mass transfer from L1-point is lost. The structure of a gas envelope, around system is calculated. 3-D mass transfer simulations has shown presence the spiral shock in the disk around primary star's and a jet-like structures (a mass flow in vertical direction) over a stream.